Pengembangan E-Modul Berbasis Higher Order Thinking Skills (HOTS) pada Materi Ikatan Kimia di SMA Negeri 17 Medan - Emilia Eka Fransiska Zebua; Muhammad Yusuf (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to develop a chemistry learning e-module based on Higher Order Thinking Skills (HOTS) on chemical bonding material for grade XI high school students. The problem in this study is the low level of higher-order thinking skills of students and the limited teaching materials that support analysis, evaluation, and creation activities. This study uses the Research and Development (R&D) method with the ADDIE model which is limited to the analysis, design, and development stages. The subjects in this study consisted of material expert validators, media expert validators, and chemistry teachers as practitioners who play a role in assessing the feasibility of the developed product. Data were obtained through a validation questionnaire and analyzed using quantitative descriptive analysis techniques by calculating the average percentage score to determine the level of product feasibility. The results showed that the developed e-module obtained a very high level of feasibility, namely 90.64% from media experts, 88.33% from material experts, and 92.95% from teacher assessments, with the category of very feasible. Thus, the developed HOTS-based e-module is declared valid in terms of content and media, and theoretically feasible for use as a digital teaching material to support the development of students' higher-order thinking skills.